Memantine-responsive catatonia secondary to tuberculosis, neurocysticercosis, and pneumococcal pneumonia: A case series - Debanjan Bhattacharjee; Ujjwal Bandyopadhyay (Indian Journal of Psychiatry)
Catatonia, a psychomotor disorder, can have underlying psychiatric and medical etiologies. Around 29% of the catatonias with medical etiologies are related to either infectious or immune causes. Benzodiazepines like lorazepam and electroconvulsive therapy are the conventional treatment modalities for catatonia. In this case series, three cases of catatonia secondary to pulmonary tuberculosis, pneumococcal pneumonia, and neurocysticercosis have been described, in which conventional treatment modalities like lorazepam or electroconvulsive therapy either failed or were disadvantageous and were successfully treated with memantine (20–30 mg).